Effects of the 2017/18 rule changes in fight duration, fight decisions, scores, penalties, and attempts in judo, based on systematic competition analysis of the World Championships 2015 and 2018 - Doppelhammer, F.; Stöckl, M. (International Journal of Performance Analysis in Sport, 2020)
The International Judo Federation (IJF) has changed the book of rules several times recently, with the last changes being implemented in 2018. Based on a systematic performance analysis, before and after the last rule changes, this research investigates how these changes have affected fight duration, fight decisions, scores, penalties, and attempts in judo. Data was collected from 308 judo fights of the World Championships 2015 in Astana and 2018 in Baku using video footage. Statistical analyses were performed in SPSS and consisted of descriptive statistics, paired T-tests and Wilcoxon tests, the effect sizes were calculated with Cohen`s d and r, respectively. The results show that the amount of fight decisions Ippon (Astana: 31.20%; Baku: 43.50%; p = .046; d = 0.59) and Wazaari-awasete-Ippon (Astana: 7.10%; Baku: 15.60%; p = .031; d = 0.65) increased, whereas the occurrence of Shido fight decisions decreased (Astana: 21.40%; Baku: 7.10%; p = .009; d = 0.50) at the 2018 World Championships, compared to 2015. No statistical differences were found between these two competitions regarding the number of attacks, attack frequencies, effectiveness and fight duration. Future research should investigate the differences between the weight categories, as well as further adjustments of judoka to the new rules.